2021
DOI: 10.1371/journal.pone.0241157
|View full text |Cite
|
Sign up to set email alerts
|

Development of an orally-administrable tumor vasculature-targeting therapeutic using annexin A1-binding D-peptides

Abstract: We previously reported that IF7 peptide, which binds to the annexin A1 (ANXA1) N-terminus, functions as a tumor vasculature-targeted drug delivery vehicle after intravenous injection. To enhance IF7 stability in vivo, we undertook mirror-image peptide phage display using a synthetic D-peptide representing the ANXA1 N-terminus as target. We then identified peptide sequences, synthesized them as D-amino acids, and designated the resulting peptide dTIT7, which we showed bound to the ANXA1 N-terminus. Whole body i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…IF7-SN38 is, however, susceptible to esterases and proteases. To circumvent stability issues, we have developed an ANXA1-binding D-peptide, designated dTIT7 [39]. We have found that GA-dTIT7, in which geldanamycin is conjugated to dTIT7 through an esterase-resistant linker, is orally administrable and suppresses brain tumor growth in the mouse.…”
Section: Author Detailsmentioning
confidence: 99%
“…IF7-SN38 is, however, susceptible to esterases and proteases. To circumvent stability issues, we have developed an ANXA1-binding D-peptide, designated dTIT7 [39]. We have found that GA-dTIT7, in which geldanamycin is conjugated to dTIT7 through an esterase-resistant linker, is orally administrable and suppresses brain tumor growth in the mouse.…”
Section: Author Detailsmentioning
confidence: 99%